Short dental implants: an emerging concept in implant treatment - Al-Hashedi, A.A.; Ali, T.B.T.; Yunus, N. (2014)
Objective: Short implants have been advocated as a treatment option in many clinical situations where the use of conventional implants is limited. This review outlines the effectiveness and clinical outcomes of using short implants as a valid treatment option in the rehabilitation of edentulous atrophic alveolar ridges. Data Sources: Initially, an electronic search was performed on the following databases: Medline, PubMed, Embase, Cochrane Database of Systematic Reviews, and DARE using key words from January 1990 until May 2012. An additional hand search was included for the relevant articles in the following journals: International Journal of Oral and Maxillofacial Implants, Clinical Oral Implants Research, Journal of Clinical Periodontology, International Journal of Periodontics, Journal of Periodontology, and Clinical Implant Dentistry and Related Research. Any relevant papers from the journals' references were hand searched. Articles were included if they provided detailed data on implant length, reported survival rates, mentioned measures for implant failure, were in the English language, involved human subjects, and researched implants inserted in healed atrophic ridges with a follow-up period of at least 1 year after implant-prosthesis loading. Conclusion: Short implants demonstrated a high rate of success in the replacement of missing teeth in especially atrophic alveolar ridges. The advanced technology and improvement of the implant surfaces have encouraged the success of short implants to a comparable level to that of standard implants. However, further randomized controlled clinical trials and prospective studies with longer follow-up periods are needed.